2013
DOI: 10.1021/op400219y
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Asymmetric Synthesis of a Renin Inhibitor: A Highly Efficient Construction Method of Three Stereogenic Centers

Abstract: An improved asymmetric synthesis of renin inhibitor DS-8108b (1) is described. This compound consists of three intermediates: 4-aminoadamantan-1-ol, ketopiperazine, and chiral lactone which contains three stereogenic centers. Especially, the chiral lactone is a key intermediate, and development of a scalable synthetic method was required, considering the quality, speed, and manufacturing cost. We established a scalable synthetic method of 1 from 4,6-O-benzylidene-d-glucose for early clinical studies. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…[58], [59], [60], [61], [62], [63], [64], [65], [66] Mindenképpen érdemes azonban megje- [69], [70], [71] Savas vagy bázikus funkciós csoportot tartalmazó olefinek esetében sóképzés [72] és/vagy pH változtatással járó extrakció alkalmazható a termék tisztítására. [73], [74], [75], [76], [77] Néhány esetben a Wittig reakció után a nyersterméket tisztítás nélkül alakítják tovább, majd egy későbbi lépésben, mikor a termék könnyebben elválasztható a foszfin-oxidtól végzik el a tisztítást. [78], [79] Fontos megjegyezni, hogy a fent említett példák csak különleges esetekben alkalmasak egyszerűsített tisztítási procedúra alkalmazására, ezért nagy jelentősége van a módosított foszfin reagensek fejlesztésének is.…”
Section: áBra a Wittig Reakció Mechanizmusaunclassified
“…[58], [59], [60], [61], [62], [63], [64], [65], [66] Mindenképpen érdemes azonban megje- [69], [70], [71] Savas vagy bázikus funkciós csoportot tartalmazó olefinek esetében sóképzés [72] és/vagy pH változtatással járó extrakció alkalmazható a termék tisztítására. [73], [74], [75], [76], [77] Néhány esetben a Wittig reakció után a nyersterméket tisztítás nélkül alakítják tovább, majd egy későbbi lépésben, mikor a termék könnyebben elválasztható a foszfin-oxidtól végzik el a tisztítást. [78], [79] Fontos megjegyezni, hogy a fent említett példák csak különleges esetekben alkalmasak egyszerűsített tisztítási procedúra alkalmazására, ezért nagy jelentősége van a módosított foszfin reagensek fejlesztésének is.…”
Section: áBra a Wittig Reakció Mechanizmusaunclassified
“…In 1984, Yoshida and co-workers reported the 1,3- trans -selective halolactonization of α-alkyl- N , N -dimethyl-4-pentenamide with N -halosuccinimide (NXS) as the halogen reagent. Since then, the 1,3- trans -selective halolactonization of chiral α-alkyl-1-oxo-4-pentenyl carbonyl compounds bearing a chiral 2-oxazolidinone framework, derived from the method of Evans et al, has been extensively utilized for the asymmetric synthesis of biological products . We have developed various oxidative transformations via umpolung of bromide from alkali metal bromide instead of organic bromo reagents, and our approach has shown that alkali metal halides, one of the most abundant natural resources on earth, are stable in air, easy to handle, neutral, and nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering work of Evans on the use of chiral N -acyloxazolidinones 1A as chiral templates for diverse asymmetric C–C bond forming reactions 1 has forged a powerful asymmetric methodology (Scheme 1), 2 which is still widely used nowadays in the total synthesis of structurally complex natural products 2,3 and medicinal agents. 4 Significantly, the 1,3-dicarbonyl nature of the imides renders the achiral N -acyloxazolidinone auxiliaries 1B as valuable bidentate substrates for catalytic asymmetric reactions. 5…”
mentioning
confidence: 99%